2022
DOI: 10.3390/ijerph19020786
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of Toxic Heavy Metal Contaminated Soil by Combining a Washing Ejector Based on Hydrodynamic Cavitation and Soil Washing Process

Abstract: Based on the features of hydrodynamic cavitation, in this study, we developed a washing ejector that utilizes a high-pressure water jet. The cavitating flow was utilized to remove fine particles from contaminated soil. The volume of the contaminants and total metal concentration could be correlated to the fine-particle distribution in the contaminated soil. These particles can combine with a variety of pollutants. In this study, physical separation and soil washing as a two-step soil remediation strategy were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 34 publications
(37 reference statements)
0
5
0
1
Order By: Relevance
“…This is because each heavy metal is extracted at different pH levels. For example, a previous study [38] performed extraction from the heavy metal-contaminated soil stabilized with cement at various pH levels (4)(5)(6)(7)(8)(9)(10)(11)(12) and reported that copper, lead, and zinc were extracted at pH 5 (Pb), 6 (Cu), and 7 (Zn) or less, respectively, and that Zn exhibited the largest elution followed by Cu and Pb at pH 4. In the present study, when heavy metals were stabilized with CKS, SLS, and ASF and then extracted using 0.1 N HCl, the extraction pH varied between 1.3 and 12.3, and Zn also exhibited the largest elution, followed by Cu and Pb, which is consistent with the previous studies (Figures [3][4][5][6][7][8][9][10][11].…”
Section: Effectiveness Of the Stabilization Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…This is because each heavy metal is extracted at different pH levels. For example, a previous study [38] performed extraction from the heavy metal-contaminated soil stabilized with cement at various pH levels (4)(5)(6)(7)(8)(9)(10)(11)(12) and reported that copper, lead, and zinc were extracted at pH 5 (Pb), 6 (Cu), and 7 (Zn) or less, respectively, and that Zn exhibited the largest elution followed by Cu and Pb at pH 4. In the present study, when heavy metals were stabilized with CKS, SLS, and ASF and then extracted using 0.1 N HCl, the extraction pH varied between 1.3 and 12.3, and Zn also exhibited the largest elution, followed by Cu and Pb, which is consistent with the previous studies (Figures [3][4][5][6][7][8][9][10][11].…”
Section: Effectiveness Of the Stabilization Treatmentmentioning
confidence: 99%
“…For example, a previous study [38] performed extraction from the heavy metal-contaminated soil stabilized with cement at various pH levels (4)(5)(6)(7)(8)(9)(10)(11)(12) and reported that copper, lead, and zinc were extracted at pH 5 (Pb), 6 (Cu), and 7 (Zn) or less, respectively, and that Zn exhibited the largest elution followed by Cu and Pb at pH 4. In the present study, when heavy metals were stabilized with CKS, SLS, and ASF and then extracted using 0.1 N HCl, the extraction pH varied between 1.3 and 12.3, and Zn also exhibited the largest elution, followed by Cu and Pb, which is consistent with the previous studies (Figures [3][4][5][6][7][8][9][10][11]. After stabilizing the heavy metals with CKS, SLS, and ASF, the leaching concentration of each heavy metal was compared; it was found that the elution of heavy metals increased as the extraction pH decreased, while Zn always showed the largest elution followed by Cu and Pb.…”
Section: Effectiveness Of the Stabilization Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous work, a washing ejector technology was used in fine particles enriched in contaminated soil with smelting-related contaminants, and it achieved remarkable results [ 28 , 29 ]. It is well known that the accumulation of metals is significantly affected by the contents of organic matter, clay minerals, and Fe oxides in contaminated soil.…”
Section: Introductionmentioning
confidence: 99%
“…As soil washing is quick and efficient, it is frequently used to remediate severely contaminated soils (Kim et al, 2022). By doing this, the amount of contaminated soil decreases and also the concentration of contaminants.…”
Section: Soil Washingmentioning
confidence: 99%